Recovering Growth : Rebuilding Dynamic Post‐COVID-19 Economies amid Fiscal Constraints - World Bank (Washington, DC: World Bank, 2021)
After its worst economic crisis in 100 years, Latin America and the Caribbean countries are emerging from the COVID‐19 pandemic. The need to recover dynamic, inclusive, and sustainable growth to redress both the legacy of the pandemic and long‐standing social needs has never been more acute. However, despite progress in some areas, the region is facing a weaker recovery than expected given the favorable international tailwinds and is likely return to the low growth rates of the 2010s. Moreover, growth could be further slowed by both internal and external factors: the emergence of a new variant of the virus, a rise in international interest rates to combat global inflation, and high levels of debt in both the private and public sector. Beyond offering the current macroeconomic outlook of the region and the near‐term challenges it faces, this report explores three broad areas where growth‐advancing policies and reforms could be undertaken within a constrained fiscal context: mobilizing sources of revenue that appear to be growth-neutral; improving public spending efficiency to free up resources for other purposes; and reallocating spending to areas with highest growth and social impact.